Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of carbon. Cast iron and pig iron: gravimetric method for the determination of non-combined carbon Part 3.8.5, (29th November 1991) - British Standards Institution
No abstract available